Far-field ammonia gas sensing at room temperature with graphene nanoplatelets-infused PEDOT:PSS transparent thin film - Vinod K Ganesan; Chun Hui Tan; Pei Song Chee; Jen Hahn Low; Soon Poh Lee; Eng Hock Lim (Talanta Open)
Amid the increasing demand for advanced gas sensing technologies, particularly for ammonia gas detection, this study presents an innovative solution for far-field sensing at room temperature. Widely used in various industrial applications, ammonia poses significant environmental and health risks, emphasizing the need for efficient monitoring. Although traditional gas sensing methods effective, they often constrained by high operating temperatures and complex electronic components, limiting their practicality. In response, transparent thin films have emerged as a promising alternative, offering real-time monitoring capabilities. However, existing transparent films often rely on external stimuli for activation, resulting in higher power consumption and degradation over time. This research investigates a transparent thin film composed of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) incorporated with graphene nanoplatelets (GNPs) for far-field ammonia gas sensing. Synthesized through a low-temperature, full-solution approach, the film demonstrates an average transmittance of 76.18 % in visible spectrum. Notably, patterning this film into a single slot antenna exhibits a significant 60 MHz frequency shift at a far-field distance of 12 cm when exposed to 50 ppm of ammonia gas. This significant frequency shift underscores the potential of the developed transparent slot antenna for practical and unobtrusive far-field sensing, advancing transparent gas sensors applications in environmental monitoring and workplace safety.